2012
DOI: 10.1002/ps.3375
|View full text |Cite
|
Sign up to set email alerts
|

Relative resistance or susceptibility of maple (Acer) species, hybrids and cultivars to six arthropod pests of production nurseries

Abstract: The results should help growers to focus pest management efforts on those plantings at greatest risk from particular pests, and to choose cultivars requiring fewer insecticide inputs to produce a quality tree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Flatheaded appletree borer has a preference for ovipositing on the lower trunk of host trees . The FHAB height preference observation led to the proposal that incorporating a plant‐related barrier to FHAB access around the base of tree trunks could protect nursery trees from attack.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Flatheaded appletree borer has a preference for ovipositing on the lower trunk of host trees . The FHAB height preference observation led to the proposal that incorporating a plant‐related barrier to FHAB access around the base of tree trunks could protect nursery trees from attack.…”
Section: Discussionsupporting
confidence: 59%
“…Temperature measurement was changed to monthly in 2017 upon evaluation of biweekly measurements in the prior year. The height of temperature measurement was chosen as 20 cm because most attacks occur at or below 20 cm …”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Similar field infestation percentages have been observed in other southeastern U.S. nurseries (Potter et al 1988;Allen & Alverson 1994;Coyle et al 2005). Given the broad host plant range of C. femorata, as well as other beetles within the C. femorata species group (Solomon 1985;Wellso & Manley 2007;Nelson et al 2008;Hansen 2010;Hansen et al 2012;Paiero et al 2012;Hansen et al in press), large numbers of tree species and cultivars are under significant risk if buprestid species are misidentified, are not monitored properly, or if management efforts are timed poorly (Troxclair 2005;Seagraves et al 2012;.…”
mentioning
confidence: 99%
“…A recent investigation of cultivar resistance indicated that ÔRed SunsetÕ red maples were most susceptible to potato leafhoppers and least sus-ceptible to maple spider mites (Seagraves et al 2013). In the same study, ÔAutumn BlazeÕ freeman maples were found to be most resistant to potato leafhopper and most susceptible to maple spider mites during midsummer.…”
mentioning
confidence: 99%